(untitled) (Advancements in Homeopathic Research, 2022)
Osteoarthritis is an important cause of disability and the second most common musculoskeletal problem in the world (30%) after back pain (50%). The prevalence of osteoarthritis increases with age. An estimated 10% to 15% of all adults aged over 60 have some degree of OA, with prevalence higher among women than men.The reported prevalence of OA in rural India is 5.8%. Homeopathy offers a wider range of options than Conventional medicine. Conventional treatment consists of anti-inflammatory drugs and corticosteroids. Long term use of these medicines can cause plenty of side-effects. This study is to know the efficiency of homeopathic medicines in the cases of Osteoarthritis, and also to make a comparative analysis of osteoarthritic nosode & constitutional medicine in the management of osteoarthritis of knee joint.